Raising Awareness of Pragmatics in the EFL Classroom: A Proposal - Irún Chavarría, Montserrat; Baiget Bonany, Ester (Cultura, Lenguaje y Representación, 2014)
The present article deals with some potential applications deriving from introducing reflection on contrastive pragmatics in EFL teaching. Specifically, it focuses on an area of politeness theory that tends to be problematic for Catalan learners of English, namely, the formulation of polite requests. The article includes a framework for the development of contrastive language awareness in the classroom and the explanation of a didactic unit intended to help learners discover the similarities and differences between polite requests in their L1 and English.